The Quakers in South Africa a social witness - Tonsing, Betty Kathryn (Rhodes University, Faculty of Humanities, Department of History, 1994)
The Religious Society of Friends, or Quakers, began their witness in the 1600s during a time of religious debate when competing doctrines reflected the political, social and intellectual turmoil of seventeenth-century England. George Fox (1624-1691), the founder, preached that people are guided by God's inner light which is present in the hearts and conscience of all people and reflects God's 'divine' will. The Quakers form a small religious membership not larger than 200,000 people sect, its world-wide. Yet, historically, the group's impact on social issues has always outweighed its numerical strength. The earliest Quakers to reside more permanently in South Africa were British settlers, several of whom became outspoken civic leaders. Quaker humanitarian gestures led to the opening of a multi-racial school for poor children in Cape Town (1840) and investigations into the treatment of Afrikaner women and children in concentration camps during the Anglo-Boer War (1899-1902). Early Quakers are also credited with initiating the Joint Council Movement of Europeans and Africans (1920s), forerunner to the South African Institute of Race Relations. This study traces the Quaker presence in South Africa from its earliest history to the present, with particular emphasis on the twentieth century. Specifically, the examination of the Quaker presence addresses the group's reaction to South African society and politics in reference to segregationist and apartheid legislation. The study includes a comparative analysis of the response among South African Quakers to these issues with Quaker response in England and the United states. The purpose of this analysis is to attempt an assessment of the extent to which South African Quaker practices were consistent with the philosophies of their world-wide religious fellowship. Relevant to the Quaker belief in peace and justice for all, with no discrimination, specific issues that involved South African Quakers and for which sufficient primary sources were available are closely examined. Of particular interest is the opening of a Quaker boarding school during the early 1930s, the Quaker response to the Defiance Campaign in 1952, and South African Quaker response to the call for international sanctions and boycotts against South Africa. More recent Quaker activities, including mediation between the African National Congress and the government, provide significant data. South African Quakers have defined themselves as members of a religious body whose belief of pacifism and commitment to non-violence dictates to a certain extent their obedience to a higher authority -- which some call their conscience and others call God -- if a civil law is deemed immoral and unjust . Thus, the study seeks to define the individual and corporate Quaker witness in South Africa in relation to the Society's principles.
Keywords: Society of Friends; Quakers -- History; Quakers -- South Africa